Project management : case studies - Kerzner, Harold (John Wiley & Sons, Inc., 2017)
The #1 Project Management case studies book now featuring new case from Disney, the Olympics, Airbus, Boeing, and more. After on-the-job experience, case studies are the most important part of every project manager's training. This fifth edition of Project Management Case Studies features more than one hundred case studies that detail projects at high-profile companies around the world. These cases offer you a unique opportunity to experience, first-hand, project management in action within a variety of contexts and up against some of the most challenging conditions any project manager will likely face. New to this edition are case studies focusing on agile and scrum methodologies. Contains 100-plus case studies from companies that illustrate both successful and not-so-successful project management; Represents an array of industries, including medical and pharmaceutical, aerospace, entertainment, sports, manufacturing, finance, telecommunications, and more; Features 18 new case studies, including high-profile cases from Disney, the Olympics, Boeing 787 Dreamliner, and Airbus 380; Follows and supports preparation for the Project Management Professional (PMP)® Certification Exam. Experienced PMs, project managers in training, and students alike will find this book to be an indispensable resource whether used as a standalone or combined with the bestselling Project Management: A Systems Approach to Planning, Scheduling, and Controlling, 12th edition.